2006
DOI: 10.1002/smi.1080
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of levels of the peptide adrenomedullin (ADM) and the enzyme tyrosine hydroxylase (TH) in rat tissue after exposure to physiological stress

Abstract: An organism's ability to respond to the external and internal environments is explained in terms of the concept of biological stress. The causes of these responses are called stressors. They may be physical, chemical, emotional, or traumatic. With continued exposure to the stressor the organism enters the stage of resistance and defense. After prolonged exposure to the same stressor the organism may enter the stage of exhaustion. Catecholamines have an important role in maintaining biological homeostasis to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…AdM has also been found to possess angiogenic, antiapoptotic, and antimicrobial properties. AdM has been examined in a variety of disease states and studies have shown the pathophysiological effects of AdM under a stress response (Yuksel and Yurekli, 2003;Yurekli and Yarpuzlu, 2006), an inflammatory reaction caused by Henoch-Schonlein purpura (HSP) (Islek et al, 2003), and an anti-inflam-matory in VEGF-induced adhesion molecules (Kim et al, 2003). AdM has also been observed in respiratory vessel endothelium dysfunction in Behcet disease (Evereklioglu et al, 2000), bipolar affective disorder (Savas et al, 2002), Bartter syndrome (Balat et al, 2002), preeclampsia (Celik et al, 2003;Hascalik et al, 2005), and varicocele and impotence .…”
Section: Discussionmentioning
confidence: 99%
“…AdM has also been found to possess angiogenic, antiapoptotic, and antimicrobial properties. AdM has been examined in a variety of disease states and studies have shown the pathophysiological effects of AdM under a stress response (Yuksel and Yurekli, 2003;Yurekli and Yarpuzlu, 2006), an inflammatory reaction caused by Henoch-Schonlein purpura (HSP) (Islek et al, 2003), and an anti-inflam-matory in VEGF-induced adhesion molecules (Kim et al, 2003). AdM has also been observed in respiratory vessel endothelium dysfunction in Behcet disease (Evereklioglu et al, 2000), bipolar affective disorder (Savas et al, 2002), Bartter syndrome (Balat et al, 2002), preeclampsia (Celik et al, 2003;Hascalik et al, 2005), and varicocele and impotence .…”
Section: Discussionmentioning
confidence: 99%